1999
DOI: 10.1177/03635465990270050801
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Passive Muscle Stiffness in Symptoms of Exercise-Induced Muscle Damage

Abstract: We examined whether passive stiffness of an eccentrically exercising muscle group affects the subsequent symptoms of muscle damage. Passive hamstring muscle stiffness was measured during an instrumented straight-leg-raise stretch in 20 subjects (11 men and 9 women) who were subsequently classified as "stiff" (N = 7), "normal" (N = 6), or "compliant" (N = 7). Passive stiffness was 78% higher in the stiff subjects (36.2 +/- 3.3 N.m.rad(-1)) compared with the compliant subjects (20.3 +/- 1.8 N.m.rad(-1)). Subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
112
3
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(126 citation statements)
references
References 32 publications
5
112
3
6
Order By: Relevance
“…When muscles such as hamstrings are stiff and subjected to eccentric exercise, strength loss, pain, muscle tenderness, and increased creatine kinase activity occurs. This is consistent with the sarcomere strain theory of muscle damage showing experimental evidence of association between flexibility and tendency to muscle injury [20]. These studies have shed light on the effects and limitations of mechanical stretching, confined to stretchable muscles, which usually are superficial.…”
Section: Discussionsupporting
confidence: 88%
“…When muscles such as hamstrings are stiff and subjected to eccentric exercise, strength loss, pain, muscle tenderness, and increased creatine kinase activity occurs. This is consistent with the sarcomere strain theory of muscle damage showing experimental evidence of association between flexibility and tendency to muscle injury [20]. These studies have shed light on the effects and limitations of mechanical stretching, confined to stretchable muscles, which usually are superficial.…”
Section: Discussionsupporting
confidence: 88%
“…Numerous studies have observed similar peak times of DOMS. [5][6][7][8] Muscle soreness likely results from myoˆbrillar damage, in‰ammatory substances sensitizing nociceptors present in damaged muscle, 19 and/or stimulation of muscle mechanoreceptors. 20 The signiˆcant increase in the ADC value of the MG at 3 days after exercise re‰ects increased motion of intramuscular water molecules.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Therefore, after eccentric exercise, in‰ammatory response and muscle dysfunction frequently occur with delayed onset muscle soreness (DOMS). [5][6][7][8] Several studies have used magnetic resonance (MR) T 2 -weighted (T 2 W) images to evaluate muscle damage induced by eccentric exercise. 6,9,10 One damage-based pathophysiological change revealed by T 2 W imaging is delayed muscle edema, which frequently occurs a few days following eccentric exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Eccentric exercises are part of regular rehabilitation as well as sports training. Unusual eccentric exercises cause muscle damage, which appears as muscle pain 2 , loss of isometric and dynamic strength 3,4 ,loss of range of motion 4 , swelling 3 , increase in muscle-specific proteins in the blood (CK, LDH) 3 and increased passive stiffness 5 . Muscle injury means mechanical rupture of the sarcomeres and pain is a result of the inflammatory response of the synthesis of prostaglandin and leucotriene 6 .…”
Section: Locomotor Apparatus In Exercise and Sportsmentioning
confidence: 99%